Narratives of Control: Settler Colonialism and the Criminalisation of Palestinian Civil Society - Lund, Caroline Karin (Trinity College Dublin. School of Religion. Discipline of Religions and Theology, 2025)
Over the past decade, most Western and European governmental donors have increasingly imposed political conditions on their funding agreements with Palestinian civil society organisations. This trend, rooted in the post-9/11 counterterrorism paradigm, reflects a broader securitisation of aid that has severely constrained meaningful civil society engagement in Palestine. Framed through a settler colonial lens, this research demonstrates how donor development policies are not neutral but are entangled withand complicit inthe Israeli settler colonial project. The escalation of donor restrictions has occurred alongside an intensifying criminalisation campaign enacted by the Israeli settler state, in which Palestinian organisations are increasingly framed as terroristic or linked to terrorist activities. Drawing on in-depth interviews with Palestinian civil society representatives and a broad range of secondary sources, this study examines how the Israeli settler state, in coordination with other Zionist and pro-Israel organisations, systematically constructs and disseminates these delegitimising narratives and uses them to pressure Western and European donors to sever their ties with Palestinian partners. It further explores the material impacts of criminalisation and the strategies organisations adopt in order to resist and survive. Ultimately, the research argues that the terrorist label functions as a central narrative tool within the broader logic of settler colonial eliminationin other words, a settler colonial strategy designed to isolate, silence, and erase Palestinian civil society.
Narratives of Control: Settler Colonialism and the Criminalisation of Palestinian Civil Society
APPROVED
Keywords: Palestine; Settler colonialism; Israel; Criminalisation; Narratives; Civil Society